Convalescent Plasma Safe, Effective and Supportive Tool During Covid-19 Pandemic- 6 Months Retrospective Study at a Tertiary Care Hospital - Mahesh C Patil; Nipun Madhav; Krishna Gopal Singh; Farah Jalaly; Madhurima Singh (International Journal of Health and Clinical Research, 2021)
Background: Convalescent Plasma (CP) is one of the promising & effective modality of massive immunization during pandemic, as currently no licensed vaccines or therapeutics are available. Systematic extraction of Single Donor Plasma (SDP) from post-Covid recovered patients by one of the useful method by Apheresis technique. Our study is to determine the role and efficacy of CP in Covid-19 infection. A total of 92 donors from Post-Covid recovered patients and their CP were extracted and collected by means of apheresis technique. 52 donors were between age group of 20 -35 yrs, 32 donors between 30 – 50yrs, 8 donors between 50-65 yrs. A total of 201 patients received CP, out of which 184 showed signs of recovery 16 reported deaths as these were severely critical & CP was ineffective in these cases. Our study has 50 control groups who did not received any convalescent therapy. In case of moderate to Severe Covid Patients, Plasma transfusion improves clinical condition and decreases mortality rates {p-value-0.001}. CP seems to be a safe and probably effective treatment for critically-ill patients with COVID-19.CP use should be encouraged to be made within the scope of clinical trials in cooperation with national and international health authorities.